Artificial Intelligence for Official Statistics: Opportunities, Practical Uses and, Challenges - Osuolale Peter Popoola (ZBW – Leibniz Information Centre for Economics, 2024)
In this era of digital transformation, artificial intelligence (AI) stands out as a revolutionary force across various sectors, including production of official statistics. Artificial intelligence is the ability of a digital computer or computer-controlled robot to perform tasks commonly associated with intelligent beings. AI technology harbors immense potential to revolutionize official statistics, from data collection, to data analysis, from data analysis to decision-making, from decision making to effective service delivery. AI tools are advancing and are becoming more prevalence. Integrating AI into official statistics by the national statistical organizations (NSOs) can be facilitated through guidance and frameworks that provide NSOs with practical knowledge on how to identify opportunities for integrating AI, assess and minimize risks, and develop phased implementation plans linked to clear lines of ownership that enable evaluation and iteration. NSOs may explore AI to enhance informed decision making, inform policies, and optimize operations. Furthermore, Safe and effective AI integration across national statistics offices have the potential to minimize administrative burdens, reduce cost against the use of traditional methods of data collection, improve decision-making and enhance public service delivery. Thus, this paper aims at developing strategies for and adopting AI capabilities for official statistics, provides guidance and frameworks for the adoption its adoption, highlights examples of how AI could be applied for official statistics, examines the governance required for responsible implementation of AI and, discusses various challenges NSOs may face when implementing Al for official statistics. Thus, providing insights into the use of AI and, the necessary conditions for ensuring responsible AI for Official statistics in this digital era.
Keywords: 330; Official Statistics; Artificial Intelligence; National Statistics Organizations; Digital Era